POSTPARTUM OBSESSIVE-COMPULSIVE DISORDER: PREVALENCE, SYMPTOMS, OUTCOMES, AND TREATMENT APPROACHES: A COMPREHENSIVE REVIEW - Izabella Sośniak; Ewa Szczęsna; Marta Miejska-Kamińska; Lidia Jurczenko (International Journal of Innovative Technologies in Social Science, 2025)
Introduction: Postpartum obsessive-compulsive disorder (PP-OCD) is a mental health condition that affects new mothers during a time of biological and emotional vulnerability. Characterized by intrusive obsessions, frequently involving fears of harming the infant, and accompanying compulsions such as checking or avoidance, PP-OCD can significantly impair maternal functioning. This review aims to synthesize current research regarding the prevalence, symptom profile, risk and protective factors, consequences, and treatment approaches for PP-OCD to improve diagnosis and intervention strategies. Description of the state of knowledge: Prevalence estimates of PP-OCD vary widely, from 1.7% to 16.9%, depending on diagnostic criteria and methodology. Obsessions typically involve harm-related intrusive thoughts, while traditional OCD features like contamination concerns are less common. Risk factors include poor sleep, prior mental illness, high neuroticism, and maladaptive cognitive interpretations. Protective traits such as resilience and hyperthymic temperament may buffer risk. There is no evidence linking PP-OCD to actual infant harm. Treatments effective in general OCD, such as CBT with ERP and SSRIs, are applicable, though specific postpartum research is still limited. Preventive CBT-based interventions show emerging promise. Conclusions: PP-OCD is a significant but underdiagnosed condition that impacts maternal well-being and can influence the bond between the infant and the mother. Increased awareness among healthcare providers and the public is essential, as misdiagnosing can lead to inappropriate care. Targeted screening, evidence-based treatments, and preventive strategies are crucial.